2018
DOI: 10.1021/acs.jmedchem.8b01536
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Selective Matriptase and Hepsin Serine Protease Inhibitors: Useful Chemical Tools for Cancer Cell Biology

Abstract: Matriptase and hepsin belong to the family of type II transmembrane serine proteases (TTSPs). Increased activity of these and the plasma protease, hepatocyte growth factor activator (HGFA), is associated with unregulated cell signaling and tumor progression through increased MET and RON kinase signaling pathways. These proteases are highly expressed in multiple solid tumors and hematological malignancies. Herein, we detail the synthesis and structure–activity relationships (SAR) of a dipeptide library bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…IGFBP7 also binds to heparan sulfate on the cell surface, but this interaction may be affected by cleavage of IGFBP7 by the trypsin-like integral-membrane serine peptidase matriptase (47). Matriptase, which cleaves substrates with Arg or Lys at the P1 position, has been incriminated in invasion and metastasis of breast cancer (48)(49)(50)(51). The action of proteolytic cleavage, specifically located at the N-terminus, including the heparin-binding motif, decreases heparin-binding and the occupancy of IGF-1R (48,52,53).…”
Section: Igfbp7mentioning
confidence: 99%
“…IGFBP7 also binds to heparan sulfate on the cell surface, but this interaction may be affected by cleavage of IGFBP7 by the trypsin-like integral-membrane serine peptidase matriptase (47). Matriptase, which cleaves substrates with Arg or Lys at the P1 position, has been incriminated in invasion and metastasis of breast cancer (48)(49)(50)(51). The action of proteolytic cleavage, specifically located at the N-terminus, including the heparin-binding motif, decreases heparin-binding and the occupancy of IGF-1R (48,52,53).…”
Section: Igfbp7mentioning
confidence: 99%
“…When overlaid on 1b, the piperidine is positioned close to the P3 amino acid nitrogen suggesting that a piperidine ring attached through a twoatom linker such as a carbamate from the P2 position would place the piperidine in a similar position to that of SRI 31215. Our previous structure-activity relationship (SAR) studies and reported PS-SCL (positional scanning of substrate combinatorial libraries) studies on matriptase, 20,29,44 hepsin 22,44,45 and HGFA 45 indicated that all three proteases require substrates with an Arg (R) at the P1 and prefer Leu (L) at the P2 position. 28,29 We hypothesize that the low potency of SRI 31215 is partly reflected by the lack of binding in the S2 pocket (Leu of 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous structure-activity relationship (SAR) studies and reported PS-SCL (positional scanning of substrate combinatorial libraries) studies on matriptase, 20,29,44 hepsin 22,44,45 and HGFA 45 indicated that all three proteases require substrates with an Arg (R) at the P1 and prefer Leu (L) at the P2 position. 28,29 We hypothesize that the low potency of SRI 31215 is partly reflected by the lack of binding in the S2 pocket (Leu of 1b). Based on this analysis and inspired by the SRI 31215 structure we designed novel hybrid dipeptide inhibitors with the preferred Leu (L) in the P2 position, but which contain the piperidine group of SRI 31215 in the P3 position installed via a carbamate from the P2 Leu as suggested by our model (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hepsin overexpression been documented in several human cancers, including renal cell carcinoma, ovarian cancer, breast cancer, endometrial cancer, and, especially, prostate cancer 27 , 28 , 29 . In fact, hepsin overexpression is one of the most consistent biomarkers for malignant transformation from benign prostate hyperplasia 30 .…”
Section: Introductionmentioning
confidence: 99%